Effect of the COVID-19 Pandemic in German Trauma Centres and Geriatric Trauma Centres DGU - Schoeneberg, Carsten; Eschbach, Daphne-Asimenia; Friess, Thomas; Lendemans, Sven; Hoefer, Christine; Ruchholtz, Steffen (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Background The COVID 19 pandemic is a major challenge to all social systems, particularly the healthcare system. Within an international study, German Trauma Centres DGU and Geriatric Trauma Centres DGU have been questioned about their situation.Method The questionnaire was translated from English into German and sent to all contacts. The evaluation was performed descriptively.Results 71 of 692 centres participated in this study. Government instructions to avoid elective treatments have been adhered to by 68% of the hospitals, and the remaining performed only urgent elective treatments. There was also a decline in the number of traumatological patients. In more than 90% of the hospitals, only 0 – 4% of all patients treated for proximal femur fracture were tested positive for COVID-19. It appears that 84% of these hospitals have or will have financial deficits. Almost all hospitals were organised and ready to fight the pandemic with their personal and/or infrastructural resources they possess.Conclusion Our questionnaire shows that the pandemic had an enormous effect on Trauma Centres DGU and Geriatric Trauma Centres DGU. The hospitals expect financial losses. Almost all the hospitals have provided personal and infrastructural resources to be used in the fight against the pandemic with a better outcome in Germany in comparison with international standards.Hintergrund Die COVID-19-Pandemie stellt neben den gesellschaftlichen auch eine große Herausforderung für das Gesundheitssystem dar. Im Rahmen einer internationalen Studie wurden die deutschen TraumaZentren DGU und AltersTraumaZentren DGU hierüber befragt.Methodik Der englische Fragebogen wurde ins Deutsche übersetzt, mit spezifischen Fragen ergänzt und durch die Akademie der Unfallchirurgie an alle Ansprechpartner der Zentren verschickt. Die Auswertung erfolgte rein deskriptiv.Ergebnisse Es nahmen 71 von 692 Zentren an der Umfrage teil. Die Vorgabe zur Einstellung von elektiven Behandlungen wurde von 68% der teilnehmenden Kliniken umgesetzt, der Rest führte nur noch dringliche Behandlungen durch. Es zeigte sich auch ein Rückgang unfallchirurgischer Patienten. Tatsächliche COVID-19-Infektionen traten bei über 90% der Kliniken nur in 0 – 4% der behandelten Patienten mit hüftgelenksnaher Femurfraktur auf. Bei 84% der Kliniken ist ein wirtschaftlicher Schaden für die Klinik eingetreten oder wird erwartet. Von fast allen Kliniken wurden personelle oder infrastrukturelle Ressourcen zur Bekämpfung der Pandemie bereitgestellt.Schlussfolgerung Unsere Umfrage zeigt, dass die Pandemie einen starken Einfluss auf die TraumaZentren DGU und AltersTraumaZentren DGU hat. Die Kliniken erwarten wirtschaftliche Einbußen. Fast alle Kliniken stellten aber personelle und infrastrukturelle Ressourcen zur Bekämpfung der Pandemie bereit und leisteten so einen Beitrag für den bisher guten Pandemieverlauf in Deutschland im internationalen Vergleich.
Keywords: COVID-19; Centre for Geriatric Trauma; Trauma Centre; IMPACT-Study; proximal femur fracture